Analisis Faktor Yang Mempengaruhi Kinerja Pegawai Puskesmas - Zulkifli Mansyur; Andi Yusuf; Muhammad Rifai (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2021)
Introduction; quality health services provided to patients are a benchmark for the success of services, and various business or service activities. Objective; analyze the factors that affect the performance of puskesmas employees. Method; The research design used in this study was observational with a Cross-Sectional Study approach with a sample of 35 Puskesmas employees. Results; show that the variables of education (ρ=0.546), work discipline (ρ=0.243), and facilities (ρ=403) have no effect on employee performance. Variables of motivation (ρ=0.000), compensation (ρ=0.000), and work environment (ρ=0.031) have an influence on the performance of employees at the Public Health Center. Conclusion; that motivation has the strongest influence on performance. The need for increased motivation, compensation and a good work environment for employees in an effort to improve employee performance